Pengaruh Waktu Ektraksi Terhadap Aktivitas Antioksidan Ekstrak Daun Rambusa (Passiflora foetida L.) Menggunakan Metode Microwave Assisted Extraction (MAE) - Ary Koesnadi, Erika; Kencana Putra, I Nengah; Sri Wiadnyani, A.A.I. (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
This research aimed to study the effect of extraction time on the antioxidant activity of rambusa leaves extracts extracted using the Microwave-Assisted Extraction (MAE) method. The extraction times were evaluated: 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes and 6 minutes with microwave irradiation power 300 Watt. This study used a completely randomized design with three repetitions to obtain 18 experimental units. The parameters observed included yield, total phenol, total flavonoids, total tannin and antioxidant activity. The data of yield, total phenol, total flavonoids, total tannin and antioxidant activity were analyzed by analysis of variance, and if the treatment had significant effect, then it was followed by the Duncan test. The results showed that extraction time significantly affected yield, total phenol, total flavonoids, total tannin and antioxidant activity of rambusa leaves extract. The results showed that 4 minutes extraction time was the best treatment, which produced a 17.40% yield, total phenol 75.07 mg GAE/g extract, total flavonoids 33.05 mg QE/g, total tannin 2.76 mg TAE/g, antioxidant activity based on free radical inhibition percentage 25.29 % and IC50 values 196.17 mg/L.